2017
DOI: 10.1002/14651858.cd012547
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver involvement in interventions for improving children's dietary intake and physical activity behaviors

Abstract: Caregiver involvement in interventions for improving children's dietary intake and physical activity behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 112 publications
0
12
0
Order By: Relevance
“…While the process we undertook to develop the Consensus Statement identified considerable evidence to substantiate the statement, it also demonstrated there are several aspects of family and child and youth movement behaviours where there are still gaps in the research literature. For example, a very recent systematic review (n = 23 studies, 1982-2019) which examined whether interventions with a parent/other adult caregiver component resulted in children being more physically active, reported little to no impact on children's activity levels [246]. The most commonly reported intervention techniques were those aimed at shaping participants' knowledge, such as providing instruction about how to perform a behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…While the process we undertook to develop the Consensus Statement identified considerable evidence to substantiate the statement, it also demonstrated there are several aspects of family and child and youth movement behaviours where there are still gaps in the research literature. For example, a very recent systematic review (n = 23 studies, 1982-2019) which examined whether interventions with a parent/other adult caregiver component resulted in children being more physically active, reported little to no impact on children's activity levels [246]. The most commonly reported intervention techniques were those aimed at shaping participants' knowledge, such as providing instruction about how to perform a behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used BCTs to categorise and understand the impact of parental support behaviour in interventions addressing child health, with improved intervention effectiveness evident when a higher number of BCTs were used, and when these were spread across behaviour change processes (Golley, Hendrie, Slater, & Corsini, 2011;Hendrie et al, 2012;Morgan, Schoonees, Faure, & Seguin, 2017;Van Der Kruk, Kortekaas, Lucas, & Jager-Wittenaar, 2013). Unsurprisingly, parental support behaviours are consistently correlated with a child's health outcomes (Gustafson & Rhods, 2006;Pyper, Harrington, & Manson, 2016;Rhodes et al, 2016).…”
Section: Behaviour Change In Health and Psychosocial Sciencesmentioning
confidence: 99%
“…Although the importance of caregivers in the development of healthy eating behaviour in children is acknowledged in most nutrition education programmes, only limited, or nonactive involvement of caregivers within the school environment is included. In addition, the active engagement of the home environment is often not taken into consideration [ 30 , 31 ]. Examples of nonactive caregiver involvement within such school-based programmes include receiving information through newsletters, folders or homework assignments.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, active involvement contains more experiential learning behaviours such as cooking together (children and caregivers at school or at home), talking about healthy eating lessons learned at school or FV provision by caregivers [ 31 , 32 , 33 ]. A recent systematic review by Morgan et al (2020) [ 30 ] assessed the effects of caregiver involvement in interventions for improving children’s dietary intake and physical activity behaviours based on 23 randomised controlled trials and concluded that there is not enough evidence to confirm added value of involving caregivers in health-promoting interventions. This lack of evidence was mainly due to the methodological limitations of these studies [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation